Characterization of three genomic loci encoding Rhizobium sp. strain ORS571 N2 fixation genes. - Donald, R G (1986)
Sixty-five independent, N2 fixation-defective (Nif-) vector insertion (Vi) mutants were selected, cloned, and mapped to the ORS571 genome. The recombinant Nif::Vi plasmids obtained in this way were used as DNA hybridization probes to isolate homologous phages from a genomic library of ORS571 constructed in lambda EMBL3. Genomic maps were drawn for three ORS571 Nif gene loci. Forty-five Nif::Vi mutants in genomic Nif locus 1 defined two gene clusters separated by 8 kilobase pairs (kb) of DNA. In the first cluster, 36 Nif::Vi mutants mapped to a 7-kb DNA segment that showed DNA homology with Klebsiella pneumoniae nifHDKE and encoded at least two Nif operons. In the other cluster, nine Nif::Vi mutants mapped to a 1.5-kb DNA segment that showed homology with K. pneumoniae and Rhizobium meliloti nifA; this DNA segment encoded a separate Nif operon. Fifteen Nif::Vi mutants mapped to a 3.5-kb DNA segment defined as Nif locus 2 and showed DNA homology with the R. meliloti P2 fixABC operon. Nif locus 2 carries a second nifH (nifH2) gene. Four Nif::Vi mutants mapped to a 2-kb DNA segment defined as Nif locus 3 and showed DNA homology with K. pneumoniae nifB. DNA from lambda Nif phages comprising all three genomic Nif loci was subcloned in plasmid vectors able to stably replicate in ORS571. These plasmid subclones were introduced into ORS571 strains carrying physically mapped Nif::Vi insertions, and genetic complementations were conducted. With the exception of certain mutants mapping to the nifDK genes, all mutants could be complemented to Nif+ when they carried plasmid subclones of defined genomic DNA regions. Conversely, most nifDK mutants behaved as pseudodominant alleles.